Analysing the impact of natural hazards in small economies: The Caribbean case - Martin Heger; Alex Julca; Oliver Paddison (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper analyses the impact of natural disasters in the Caribbean. The economic impact of natural disasters in the region has been significant, resulting in widespread destruction of the productive economy. This paper presents the main macroeconomic impact of disasters, e.g., a deteriorating fiscal balance, a collapse of growth and a worsening external balance, as a consequence of damage resulting from the event. By making special reference to the small-island developing state nature of many countries in the region, valuable lessons of the impact of such disasters on the capital stock can be learnt, particularly as the interruption of production of goods and services can be particularly devastating in an environment where few large sectors (agriculture, tourism) dominate the economic landscape.
Keywords: Q54; O54; L25; F14; 330; natural disasters; Caribbean; diversification; trade and environment; Naturkatastrophe; Kleines-Land-Modell; Makroökonomischer Einfluss; Karibische Staaten